Trend of changes in ATP and WTA tennis players` age and anthropometric parameters in the period from 2000 to 2019 - Laskovic, M. (Serbian Journal of Sports Sciences, 2020)
The aim of this study was to determine if any trend changes have appeared in professional tennis players` age and basic anthropometric characteristics in the period from 2000 to 2019. Top 20 ranked tennis players, both male and female, for each competitive season were a sample in this study. The variables used in the analysis were the players` age, body height, body mass and body mass index. Regression analysis was used to calculate linear trends between examined variables in the function of years as an observed competitive season. A statistically significant increase has been noted in male players` age (R²=0.7258, p=0.000), body height (R²=0.6614, p=0.000) and body mass (R²=0.4948, p=0.001), whilst a significant decrease was found in body mass index (R²=0.4261, p=0.001). When it comes to female players, the only statistically significant change was in their age (R²=0.5587, p=0.000). The results indicate that competitive experience became more influential on the performance of the top 20 ranked ATP and WTA players, while anthropometric characteristics are only changing in men.